Approximation method for a fractional order transfer function with zero and pole - Oprzędkiewicz Krzysztof (Archives of Control Sciences, 2014)
The paper presents an approximation method for elementary fractional order transfer function containing both pole and zero. This class of transfer functions can be applied for example to build model - based special control algorithms. The proposed method bases on Charef approximation. The problem of cancelation pole by zero with useful conditions was considered, the accuracy discussion with the use of interval approach was done also. Results were depicted by examples.